2016
DOI: 10.1155/2016/5614747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Jia‐Wei‐Xiao‐Yao‐San on the Peripheral and Lymphatic Pharmacokinetics of Paclitaxel in Rats

Abstract: Paclitaxel is effective against breast cancer. The herbal medicine, Jia-Wei-Xiao-Yao-San (JWXYS), is the most frequent prescription used to relieve the symptoms of breast cancer treatments. The aim of the study was to investigate the herb-drug interaction effects of a herbal medicine on the distribution of paclitaxel to lymph. A validated ultraperformance liquid chromatography with tandem mass spectrometry (UPLC-MS/MS) method was used to determine the paclitaxel levels in rat plasma and lymph after intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Additionally, paclitaxel is approved as a first-line therapy for metastatic breast cancer and has been likely administered with JWXYS in Taiwan; therefore, an investigation of the impact of JWXYS during coadministration with paclitaxel from a pharmacokinetic perspective is valuable for providing information for clinical users. Hou et al studied the herb–drug interactions of JWXYS and paclitaxel in rodent species [ 34 ], and reported that the plasma AUC of paclitaxel in the paclitaxel alone group was approximately 1.5-times higher than that in the group that received oral JWXYS daily for seven days and a single dose of paclitaxel. Furthermore, after pretreatment with JWXYS for seven days, the half-life of paclitaxel increased from 73 min to 111 min, and the clearance increased approximately 1.4-fold compared to paclitaxel alone [ 33 ].…”
Section: Concurrent Use Of Traditional Chinese Formulations and Cance...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, paclitaxel is approved as a first-line therapy for metastatic breast cancer and has been likely administered with JWXYS in Taiwan; therefore, an investigation of the impact of JWXYS during coadministration with paclitaxel from a pharmacokinetic perspective is valuable for providing information for clinical users. Hou et al studied the herb–drug interactions of JWXYS and paclitaxel in rodent species [ 34 ], and reported that the plasma AUC of paclitaxel in the paclitaxel alone group was approximately 1.5-times higher than that in the group that received oral JWXYS daily for seven days and a single dose of paclitaxel. Furthermore, after pretreatment with JWXYS for seven days, the half-life of paclitaxel increased from 73 min to 111 min, and the clearance increased approximately 1.4-fold compared to paclitaxel alone [ 33 ].…”
Section: Concurrent Use Of Traditional Chinese Formulations and Cance...mentioning
confidence: 99%
“…Furthermore, after pretreatment with JWXYS for seven days, the half-life of paclitaxel increased from 73 min to 111 min, and the clearance increased approximately 1.4-fold compared to paclitaxel alone [ 33 ]. Interestingly, JWXYS rarely affected the lymphatic absorption rate or the lymphatic distribution, but it influenced the metabolic enzymes and intestinal absorption, resulting in an obvious reduction in plasma paclitaxel levels [ 34 ].…”
Section: Concurrent Use Of Traditional Chinese Formulations and Cance...mentioning
confidence: 99%